Early and late changes in sulphydryl group and copper protein concentrations and activities during drug treatment with aurothiomalate and auranofin. - Rae, K J (1986)
Superoxide dismutase activity (SOD), plasma and lysate thiol concentrations (PSH and LSH), and caeruloplasmin oxidase activity (CP) reflect the underlying reduction-oxidation imbalance associated with rheumatoid arthritis (RA), and are believed to be involved in the protection of the cell against free radical activity. The early and late changes in these parameters have been observed and compared with standard clinical and biochemical assessments of disease activity in 90 patients with active RA, randomly assigned to receive either sodium aurothiomalate, auranofin, or auranofin placebo. An index based on clinical criteria was used to identify patients as responders or non-responders after 24 weeks of therapy. In the first six weeks of treatment a change in SOD activity and LSH concentration in a direction away from controls was followed by a return towards control levels in responders only. This suggests that in RA evidence of clinical improvement induced by gold drugs is preceded by an initial biochemical response in an inflammatory direction. The extracellular parameters PSH and CP did not show the same early response, but PSH levels in responders showed a slower change towards normal values, though at no time were values obtained that might suggest a complete remission. Thus the intracellular parameters appear to reflect an early effect of the drugs on cells which may possibly be of use in predicting the outcome of therapy, whereas the extracellular parameters provide confirmatory evidence for an eventual improvement.